INTEGRATION OF STUDYING THE DISCIPLINES OF DISCRETE MATHEMATICS AND COMPUTER SCIENCE IN THE SYSTEM OF TRAINING IT SPECIALISTS - Umarov, Xasan (Журнал иностранных языков и лингвистики, 2022)
This paper discusses the issues of integrated study of discrete mathematics and informatics in the system of training IT specialists. The features and possibilities of interaction of such disciplines as computer science and discrete mathematics at the level of study in higher education are considered. The special attention paid to IT specialists is not accidental, since the development of computer technology is one of the most promising areas of science in modern society. The formation of algorithmic competence and systemic thinking, the ability to apply their knowledge not only in the study of individual disciplines, but also in the complex mastering of the disciplines of the entire training program - these are the priority tasks of teachers working with future professionals. Professional competence for graduates of professional educational organizations is specific and meets the requirements for technicians working in the field of information technology. It includes intellectual competence, communication, general cultural, etc. One of the main components of professional competence is intellectual competence, in which the main component for graduates of professional educational organizations is algorithmic. It is this basic competence that is most effectively formed in the integrated study of discrete mathematics and computer science.